KEMAMPUAN MANAJERIAL KEPALA SEKOLAH MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MTs NEGERI 1 BATANGHARI - Hendri (Jurnal Ilmiah Bina Edukasi, 2025)
This study highlights the managerial role of the Head of Madrasah in improving teacher performance at MTs Negeri 1 Batanghari, driven by a lack of supervision, motivation, and monotonous teaching methods. The research method uses a qualitative approach with descriptive analysis. The results show that the Head of Madrasah has carried out the planning function well, inling all components of the school. In terms of organization, the Head of Madrsasah has assigned duties and responsibilities to each personnel according to their fields. The mobilization has been conducted effectively, although the results are not yet optimal. Supervision and evaluation have also been carried out fairly well, though there is room for improvement. The challenges faced include teachers’ lack of understanding of the curriculum and low motivation for self-development. The strategies implemented by the Head of Madrasah to improve teacher performance include motivating work spirit, setting a good example, providing rewards, appropriate task assignments, and classroom visits.